Análisis bioético de la violencia obstétrica en el ecuador y la implementación de protocolos de prevención y erradicación - Rosales Cedeño, Kenyi Nicole (2025)
Obstetric violence, characterized by acts of aggression against pregnant women during the prenatal, perinatal, and postnatal stages, has long been an unnoticed issue, involving attitudes and practices that go against medical ethics. Nowadays, thanks to movements advocating women's rights, this issue has gained visibility, leading to the development of protocols and strategies aimed at its elimination. Objective: To analyze obstetric violence statistics in Ecuador from a bioethical perspective, along with the protocols that have been implemented, in order to propose potential suggestions and/or considerations as part of the efforts to raise awareness and eradicate obstetric violence. Methods: A descriptive study was carried out through a documentary analysis of the topic. Results: In Ecuador, it is estimated that around 40% of women who are mothers have experienced some form of mistreatment during pregnancy. As a result, two protocols have been established: ESAMyN and the Comprehensive Care Protocol for Victims of Gender-Based Violence and Serious Human Rights Violations. Both aim to safeguard the well-being of pregnant and non-pregnant women; however, there is evidence of poor compliance. Conclusion: Obstetric violence remains a significant challenge in Ecuador that requires ongoing efforts. Despite the existing initiatives, the data show that cases of gynecological-obstetric mistreatment still occur, highlighting the need to implement strategies that ensure compliance.